Determinan Minat Mengunakan Aplikasi Akuntansi Mobile Pada Umkm Kota Palangka Raya Dalam Menghadapi Revolusi Industri 4.0: Sebuah Pendekatan Technology Acceptance Model - Kharisma Nugraha Putra; Merisa Oktaria; Alexandro, Rinto; Winda Lestiani (FKIP, Universitas Palangka Raya, 2024)
This research adopts the Technology Acceptance Model to examine the factors that influence interest in using mobile accounting applications for financial recording. The purpose of this research is to examine the influence of perceived convenience and perceived usefulness on interest in using mobile accounting applications for financial recording. The sample in this research is UMKM in Palangka Raya. The data collection method is a survey using a questionnaire as a research instrument. The number of samples was 100. Data were analyzed using Structural Equation Modeling-Partial least squares (SEM-PLS) with the Warp PLS 8 program. The results of the study found that perceived ease of use and perceived usefulness had a positive effect on interest in using mobile accounting applications